Kecemasan Menghadapi Mutasi Ditinjau dari Self Efficacy Pada Karyawan Pabrik Sawit - Natura, Belly; Kurniawan, Harri; Mutya, Mita Fani Tri; Muliati, Riska (Indonesian Research Journal on Education, 2025)
This study aims to determine the relationship between self-efficacy and anxiety in facing mutations in employees of pabrik sawit. The independent variable in this study is Self Efficacy and the dependent variable is anxiety. The measuring instruments used in this study were the Self Efficacy scale and the Anxiety scale. The sampling technique in this study using saturated sampling technique. The sample in this study were 47 employees of pabrik sawit. Validity and Reliability Test in this study used Alpha Cronbach technique. The item difference index on the Self-efficacy scale moves from rix = 0.304 to rix= 0.799 with a reliability coefficient of α = 0.930. Meanwhile, the anxiety scale moves from rix = 0.376 to rix = 0.734 with a reliability coefficient of α = 0.937. Based on the results of data analysis, it can be concluded that there is a significant relationship between Self Efficacy and Anxiety, with a correlation value (r) of -0.799 with a significant level of 0.000, which means that the hypothesis is accepted. This shows that there is a significant negative relationship between Self Efficacy and dealing with mutations in the process division employees of pabrik sawit .